(untitled) (Research, Society and Development, 2020)
Objective: To determine the survival rate of COVID-19 in Bogotá-Colombia between March and July 2020. Materials and Methods: a retrospective cohort study was made in a population infected by COVID-19 in Bogotá from March 6 to July 8, 2020. Incomplete data was excluded and data reported to the INS were used. Infected populations were confirmed via PCR test; the study time starts intiates during onset of symptoms until death or the final time of the cohort. For survival, the actuarial method, the Long-Rank test, was applied. Results: Survival rate on days 1, 10, 20 and 30, is of 100%, 99%, 98% and 96% respectively, (p <0.01) survival rate at 30 days in female sex is 97% and 95% male patients (HR = 1.4 95% CI 1.2-1.6), the 30-day survival rate of hospitalized patients is of 76%, and 100% in non-hospitalized patients (HR = 31.2 95% % 24.4-40), the age group with the lowest survival rate of 63% was the ≥80 years group (HR = 48.4 95% CI 27.5-85.2). Conclusion: The risk factors related to mortality in Bogotá-Colombia are male sex, advanced age, and hospitalization. The last two risk factors mentioned are risk factors known across multiple COVID-19 survival studies in different ethnic groups and locations. Meanwhile, male sex is not an universal risk factor, not seen in certain studies with different populations and ethnic groups.